Systems Of Computer Mathematics And Their Role In Mathematical Education (Journal of Information Technologies in Education (ITE), 2009)
In the article the matter is about software of Computer Mathematics. The opportunity of application is considered and the role of systems of Computer Mathematics in Mathematics training and in mathematical education is determined.
Keywords: Computer Mathematics; information training environments; mathematical disciplines training technique; software; systems of Computer Mathematics